ANALISIS PENGARUH TEMPERATUR HOT PRESS TERHADAP PENINGKATAN NILAI FRAKSI β FILM PVDF - Ahmad Novi Muslimin; Ambran Hartono; Arif Tjahjono; Nurul Fadilah; Priyambodo Priyambodo (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
PVDF film is a piezoelectric material that is still being developed as transducer and piezoelectric sensor. It is caused by the piezoelectric constant and the mechanical properties of PVDF are larger than the existing polymer piezoelectric. The high demand for the use of PVDF films makes it possible to make low-cost PVDF films with high piezoelectric properties. There are a variety of techniques used to make PVDF films especially PVDF films that have high Î²-phase fractions. In this research, PVDF film was made using simple hot press, at temperature 165á´¼C, 180á´¼C and 195á´¼C and heating time 15, 30 and 45 minutes. From the research results, PVDF film produced with the smallest thickness of 200Î¼m and the largest is 345Î¼m. The largest fraction of Î² obtained was 40.47% at 180 Â° C with 30 minutes heat heating time and the smallest fraction of Î² obtained was 31.05% at a hot press temperature of 165 á´¼C at heating time of 45 minutes. Based on the value of Î² fraction obtained, at a press temperature of 180 á´¼C and a 30 minute heating time is aÂ  good process used for PVDF filmmaking.Keywords: PVDF film, hot press, Î² fraction, piezoelectric.